Hydrocarbon degradation by Antarctic coastal bacteria - Cavanagh, JE; Peter Nichols; Franzmann, PD; Thomas McMeekin (1998)
Bacterial cultures obtained through selective enrichment of beach sand collected 60 days and one year after treatment of sites in a pilot oil spill trial conducted at Airport Beach, Vestfold Hills, East Antarctica, were examined for the ability to degrade n-alkanes and phenanthrene. The effects of different hydrocarbon mixtures (Special Antarctic Blend [SAB] and BP-Visco), fish oil [orange roughy]) and inoculation of replicate sites with water from Organic Lake (previously shown to contain hydrocarbon-degrading bacteria) on the indigenous microbial population were examined. Of the cultures obtained, those from sites treated with SAB and BP-Visco degraded n-alkanes most consistently and typically to the greatest extent. Two mixed cultures obtained from samples collected at 60 days and two isolates obtained from these cultures extensively degraded phenanthrene. 1-Hydroxy-naphthoic acid formed the major phenanthrene metabolite. Lower levels of salicylic acid, 1-naphthol, 1,4-naphthaquinone and phenanthrene 9-10 dihydrodiol were detected in extracts of phenanthrene grown cultures. This study shows that under laboratory conditions indigenous Antarctic bacteria can degrade n-alkanes and the more recalcitrant polycyclic aromatic hydrocarbon, phenanthrene. The enrichment of hydrocarbon degrading microorganisms in Antarctic ecosystems exposed to hydrocarbons is relevant for the long term fate hydrocarbon spills in this environment.